Cultural Differences in Answerability Judgments - Karlsson, Bodil S. A.; Allwood, Carl Martin (Frontiers in Psychology, 2018)
Judgments about whether anyone can provide a relevant and correct answer to a question are called answerability judgments. Such judgements can be important in societal planning and decision making and may vary in different cultural contexts. Six hundred participants in each of China, India and Sweden made answerability judgments of 6 difficult knowledge questions. For each question they choose between three options indicating that they thought the question was answerable and a fourth option: “Nobody can answer that question”. After each question they rated their confidence that their judgment was correct. Choosing “Nobody can answer that question” was significantly more common for the Swedes and was uncommon in the Asian samples. The Asian samples showed higher confidence in their judgments. We suggest that these differences may be explained by results from cross-cultural research, but this study did not investigate specific mechanisms. Hence more research is needed.